GE_GERICHTE P/5118/2014 vom 14. April 2015 - GE Cour de justice (2015)
MISE EN DANGER DE LA VIE D'AUTRUI(ART. 129 CP); VOL(DROIT PÉNAL); LÉSION CORPORELLE SIMPLE; ÉTAT DE NÉCESSITÉ | CPP.10.3; CP.123; CP.129; CP.139; CP.18; CP.63